A War of Colors Graffiti and Street Art in Postwar Beirut - Sinno, Nadine A. (University of Texas Press, 2024)
Demonstrates the role of Beirut's postwar graffiti and street art in transforming the cityscape and animating resistance. Over the last two decades in Beirut, graffiti makers have engaged in a fierce "war of colors," seeking to disrupt and transform the city's physical and social spaces. In A War of Colors, Nadine Sinno examines how graffiti and street art have been used in postwar Beirut to comment on the rapidly changing social dynamics of the country and region. Analyzing how graffiti makers can reclaim and transform cityscapes that were damaged or monopolized by militias during the war, Sinno explores graffiti's other roles, including forging civic engagement, commemorating cultural icons, protesting political corruption and environmental violence, and animating resistance. In addition, she argues that graffiti making can offer voices to those who are often marginalized, especially women and LGBTQ people. Copiously illustrated with images of graffiti and street art, A War of Colors is a visually captivating and thought-provoking journey through Beirut, where local and global discourses intersect on both scarred and polished walls in the city